Fragmentary data and scattered lands: a recording protocol for a comparative archaeothanatological analysis based on archaeological illustrations - Anastasia Chrysanthi Solomou (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
This paper examines the treatment of the dead in three Early Bronze Age cemeteries on the Greek mainland, in comparison with six contemporaneous cemeteries in the Cyclades. The study presented here was undertaken with a view to exploring whether and to what extent differences in mortuary practices can be identified between the two regions, as part of the wider discussion regarding Cycladic and Cycladic-style artefacts and architecture in mainland cemeteries. The study aimed to reconstruct practices in the case-studies by devising a protocol for recording human remains from illustrations. The protocol is based on archaeothanatological principles and structured by a decision tree to ensure comparability and repeatability. The results highlight aspects of differentiation between Tsepi, Aghios Kosmas (mainland) and the Cyclades, indicating variation in mortuary practices: for example, the graves at Tsepi, and potentially at Aghios Kosmas, were filled in following each deposit whereas the Cycladic case-study graves were left uncovered. Differences were also observed in the architectural setting of the secondary interferences. The interpretation for Manika, on Euboea, however, is more problematic, since it presents common features with the case-studies in both the Cyclades and the mainland.